2020
DOI: 10.1101/2020.12.23.20248598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic characterization of a novel SARS-CoV-2 lineage from Rio de Janeiro, Brazil

Abstract: In this study, we report the sequencing of 180 new viral genomes obtained from different municipalities of the state of Rio de Janeiro from April to December 2020. We identified a novel lineage of SARS-CoV-2, originated from B.1.1.28, distinguished by five single-nucleotide variants (SNVs): C100U, C28253U, G28628U, G28975U, and C29754U. The SNV G23012A (E484K), in the receptor-binding domain of Spike protein, was widely spread across the samples. This mutation was previously associated with escape from neutral… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
205
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(212 citation statements)
references
References 27 publications
7
205
0
Order By: Relevance
“…In particular, a lot of attention has been focused on RBD mutation E484K, which has emerged in multiple independently SARS-CoV-2 lineages 63, 64 and can alter the antigenicity of the spike protein [65][66][67] . Another naturally occurring RBD mutation, K417N, which has emerged in South Africa and Brazil (B.1.351 lineage and B.1.1.28, respectively) 63, 64,68 , has recently been shown to also alter antigenicity of the spike protein 66,[69][70][71] . Consistently, we found that K417N dramatically decreased the binding of COV107-23 (clonotype 1) and COVD21-C8 (clonotype 2)…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a lot of attention has been focused on RBD mutation E484K, which has emerged in multiple independently SARS-CoV-2 lineages 63, 64 and can alter the antigenicity of the spike protein [65][66][67] . Another naturally occurring RBD mutation, K417N, which has emerged in South Africa and Brazil (B.1.351 lineage and B.1.1.28, respectively) 63, 64,68 , has recently been shown to also alter antigenicity of the spike protein 66,[69][70][71] . Consistently, we found that K417N dramatically decreased the binding of COV107-23 (clonotype 1) and COVD21-C8 (clonotype 2)…”
Section: Discussionmentioning
confidence: 99%
“…Its appearance is likely to have arisen independently (Faria et al, 2021) . In Brazil, the E484K mutation (glutamic acid to lysine substitution at amino acid 484) also arose independently and was identified in Rio de Janeiro state (Southeast Brazil) in early-October in P.2 lineage (Voloch et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…After more than a year of the COVID-19 pandemic, new circulating variants of SARS-CoV-2 have been described that show resistance against the immune response of previously immunized individuals 1,2 or available therapeutics 3,4 . In many regions around the globe, governments are implementing lock-down measures to contain rapidly spreading SARS-CoV-2 spike variants associated with increased transmissibility 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently identified variants in the UK (B.1.1.7 lineage), South Africa (B.1.351 lineage) 6 and Brazil (P.1. lineage) 2 share mutations on the spike protein, which have evolved independently.…”
Section: Introductionmentioning
confidence: 99%